2016
DOI: 10.1007/s00417-016-3444-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperbaric oxygen versus iloprost treatment in an experimental rat central retinal artery occlusion model

Abstract: The study results demonstrated anti-edema, neuroprotective, and anti-apoptotic effects of iloprost quantitatively; thus, iloprost may be a beneficial alternative agent in the treatment of CRAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…HBOT also decrease edema and preserve compromised tissue adjacent to ischaemic area [1,2,8]. Karaman et al demonstrated, in mice models of CRAO, that the apoptotic index of retinal inner cells was lower in the group submitted to HBOT in the reperfusion phase than in control group [12]. Also in an animal experiment in a CRAO mice model, Gaydar et al showed that HBOT diminished cell loss from 58% to 30%, which was related to increased survival of cells in the retinal inner layer [13].…”
Section: Introductionmentioning
confidence: 99%
“…HBOT also decrease edema and preserve compromised tissue adjacent to ischaemic area [1,2,8]. Karaman et al demonstrated, in mice models of CRAO, that the apoptotic index of retinal inner cells was lower in the group submitted to HBOT in the reperfusion phase than in control group [12]. Also in an animal experiment in a CRAO mice model, Gaydar et al showed that HBOT diminished cell loss from 58% to 30%, which was related to increased survival of cells in the retinal inner layer [13].…”
Section: Introductionmentioning
confidence: 99%